Prospective randomised controlled trial of methods of call and recall for cervical cytology screening. Issue 6692 (15th July 1989) - Pierce, M.; Lundy, S.; Palanisamy, A.; Winning, S.; King, J.
Abstract : OBJECTIVE–To discover whether systematic methods of call and recall are more effective than a non-systematic method and to see which of the two systematic methods was more effective. DESIGN–Prospective randomised controlled trial over a year. SETTING–One group general practice. PATIENTS–416 Women over 35 eligible for a smear test who had never had a cervical smear test or in whom a smear test was overdue (previous test more than five years before). INTERVENTIONS–One group received written invitations to have a smear taken. The second group had their notes tagged so that the doctor would remind them (when they attended for another reason) to have a smear test. No special intervention was made in the third group. MAIN OUTCOME MEASURE–Performance of a cervical smear test during the year of the study. RESULTS–32% (45/140) of the screened group, 27% (39/142) of the tagged group, and 15% (20/134) of the control group had a smear test during the year. The percentage of women having a smear test in the screened group was not significantly different from that in the tagged group, but the percentages in the two groups were significantly different from that in the control group. Whether a woman had had a previous smear test significantly affected the uptake of the invitation to have a smear test independently of the method of invitation. CONCLUSIONS–The systematic methods of call and recall were more effective than a non-systematic method. There was no significant difference between the two systematic methods (sending letters or tagging the notes) at one year.